Food Processing Learning Strategies for Vocational High School Students Majoring in Culinary Arts in Tondano, Minahasa Regency: Opportunities and Challenges - Louisa Kandoli (Indonesian Journal Publisher, 2025)
This study aims to analyze learning strategies for processing food applied to students of Vocational High School (SMK) majoring in culinary arts in Tondano, Minahasa Regency, and to examine the opportunities and challenges faced in the implementation process. Research: This use-method study literature with a qualitative approach combined with contextual analysis. Search article in the Scopus database, with publications from 2020–2026, using the keywords